2021
DOI: 10.1159/000515845
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/dCas9 as a Therapeutic Approach for Neurodevelopmental Disorders: Innovations and Limitations Compared to Traditional Strategies

Abstract: Brain development is a complex process that requires a series of precise and coordinated events to take place. When alterations in some of those events occur, neurodevelopmental disorders (NDDs) may appear, with their characteristic symptoms, including cognitive, social motor deficits, and epilepsy. While pharmacologic treatments have been the only therapeutic options for many years, more recently the research is turning to the direct removal of the underlying genetic cause of each specific NDD. This is possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 103 publications
0
11
0
Order By: Relevance
“…Here, it is discussed that using these inhibiting molecules as therapeutic approach, this also promotes the activation of oncogenes and potentially increases cancer risk ( Mastrototaro and Sessa, 2018 ). Thus, current research aims to investigate target-specific treatment of NDDs, for which the CRISPR/Cas9 system is suggested to serve as potential approach ( Ricci and Colasante, 2021 ). Recently, it has been exploited to recover the haploinsufficiency of Scn1a in mice, known to be essential in the development of different forms of epilepsy ( Supplementary Table S1 ; Staley, 2015 ; Ricci and Colasante, 2021 ).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, it is discussed that using these inhibiting molecules as therapeutic approach, this also promotes the activation of oncogenes and potentially increases cancer risk ( Mastrototaro and Sessa, 2018 ). Thus, current research aims to investigate target-specific treatment of NDDs, for which the CRISPR/Cas9 system is suggested to serve as potential approach ( Ricci and Colasante, 2021 ). Recently, it has been exploited to recover the haploinsufficiency of Scn1a in mice, known to be essential in the development of different forms of epilepsy ( Supplementary Table S1 ; Staley, 2015 ; Ricci and Colasante, 2021 ).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Thus, current research aims to investigate target-specific treatment of NDDs, for which the CRISPR/Cas9 system is suggested to serve as potential approach ( Ricci and Colasante, 2021 ). Recently, it has been exploited to recover the haploinsufficiency of Scn1a in mice, known to be essential in the development of different forms of epilepsy ( Supplementary Table S1 ; Staley, 2015 ; Ricci and Colasante, 2021 ). Another study used the Cas9-system to specifically recruit multiple DNMT3A catalytic domains to Sema6a promoter in post-mitotic and -migratory glutamatergic cortical neurons, leading to rescued impairments of interhemispheric connections, which are described for ASD or SZ ( Ricci and Colasante, 2021 ).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…CRISPR/Cas9-mediated genome engineering is quite precise and straightforward due to the target specificity and simple design of gRNA. Studies employing CRISPR have already exhibited efficiency in preclinical models of neurological disorders ( Gaj et al, 2017 ; Yang et al, 2017 ; György et al, 2018 ; Lee et al, 2018 ; Ekman et al, 2019 ; Ricci and Colasante, 2021 ). Moreover, a recent report suggests that CRISPR technology is in fact promising in clinical trials ( Frangoul et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…CRISPR/Cas9 is one of the most widely used gene editing tools due to the simple design of the sgRNA giving it a combination of precision and ease of use. Studies employing CRISPR have already exhibited treatment efficiency in preclinical models of neurological disorders. Several pioneering studies have demonstrated that gene editing in the brain with Cas9 using nonviral delivery vehicles is possible. Specifically, Staahl et al demonstrated that direct injection of the Cas9 protein fused to 6 SV40 nuclear localization signals (4xNLS-Cas9-2xNLS) complexed to sgRNA (4xNLS-Cas9-2xNLS RNPs) into the striatum and hippocampus of Ai14 mice was able to edit genes in brain tissue efficiently .…”
mentioning
confidence: 99%